Are you getting enough? - Dowden, Angela (Orion Paperback, 1999)
A practical and accessible book explaining the benefits of the vitamins and minerals present in food...What they are, what they do and why they are so important to our general health. There are a plethora of confusing facts surrounding our dietary requirements from RDAs recommended daily amounts to optimal intake explained and explored in turn, plus the latest information on the safe upper levels of vitamin intake. The book also includes an A to Z of vitamins and minerals and their sources and a detailed look at the changing needs of the body throughout the various life stages from childhood to old age, pregnancy to menopause.